Long-term results and comparison of the Green-Anderson and multiplier growth prediction methods after permanent epiphysiodesis using Canale's technique. (1st August 2019) - Burger, K.; Farr, S.; Hahne, J.; Radler, C.; Ganger, R.
Abstract: Purpose: The aim of the study was to evaluate the accuracy and radiographic outcomes of Canale's method in patients with idiopathic leg-length discrepancy (LLD) following percutaneous epiphysiodesis. The accuracy of two common growth prediction methods was assessed. Methods: A total of 18 patients with 26 affected bones (eight distal femur, two proximal tibia, five combined) were clinically and radiologically analyzed after reaching skeletal maturity. We compared the final effect of epiphysiodesis at maturity with the expected effect of epiphysiodesis before surgery; these measures were calculated using the Green-Anderson and multiplier methods, respectively. We furthermore compared pre- and postoperative frontal and lateral plane radiographs. Results: The average LLD was 21.2 mm before surgery and 7.9 mm after epiphysiodesis. The final effect of both methods was not significantly different compared with the expected effect of epiphysiodesis before surgery. However, the prediction by the Green-Anderson method was closer to the definitive epiphysiodesis effect. The frontal plane radiographic deformity parameters did not change significantly after epiphysiodesis. The postoperative sagittal plane radiographic deformity parameters were in the normal range. Conclusion: The Canale technique is a reliable method to reduce LLD in children. With regards to growth prediction, the Green-Anderson method using bone age seems to be more accurate than the multiplier method using chronological age. However, a relative over-estimation was observed with both methods in several cases, which might result in an insufficient correction. Level of Evidence: IV, Therapeutic study